IDENTIFIKASI POTENSI KOMUNITAS DALAM PEMBERDAYAAN MASYARAKAT BERBASIS ECOVILLAGE : (Studi kasus di Dusun Dukuh, Desa Penebel, Tabanan) - Gede Nyoman Wiratanaya; Ni Putu Dyah Krismawintari; Raden Agus Sarwa Edy (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Creating and rehabilitating a large number of small and sustainable habitats to empower communities based on ecovillages is the heartbeat of a sustainable natural system, which is expected to be able to improve the community's economy, as one of the achievements to reduce the ecological footprint. Bhakti Ring Pertiwi (B-Riper) is a local community based in Dukuh Hamlet, Penebel Village, Tabanan Regency, routinely carrying out voluntary social and cultural movements aimed at preserving the environment, especially for handling piles of garbage that occur along the Yeh River watershed. Empas, which flows and at the same time becomes the source of life for the community around the village. This study uses a qualitative verification design. Through a SWOT analysis approach looking at the strengths, weaknesses, opportunities and threats that exist, several strategies were found that can be used by the community in developing the potential of Dukuh Hamlet, Penebel Village, Tabanan Regency, Bali as a tourist attraction to realize increased community empowerment.